Extracellular vesicles: an emerging player in retinal homeostasis - Chatterjee, Amit; Singh, Ruchira (Frontiers in Cell and Developmental Biology, 2023)
Extracellular vesicles (EVs) encompass secreted membrane vesicles of varied sizes, including exosomes (∼ 30-200 nm) and microvesicles (MVs) that are ∼100-1000 nm in size. EVs play an important role in autocrine, paracrine, and endocrine signaling and are implicated in myriad human disorders including prominent retinal degenerative diseases, like age related macular degeneration (AMD) and diabetic retinopathy (DR). Studies of EVs in vitro using transformed cell lines, primary cultures, and more recently, induced pluripotent stem cell derived retinal cell type(s) (e.g., retinal pigment epithelium) have provided insights into the composition and function of EVs in the retina. Furthermore, consistent with a causal role of EVs in retinal degenerative diseases, altering EV composition has promoted pro-retinopathy cellular and molecular events in both in vitro and in vivo models. In this review, we summarize the current understanding of the role of EVs in retinal (patho)physiology . Specifically, we will focus on disease-associated EV alterations in specific retinal diseases. Furthermore, we discuss the potential utility of EVs in diagnostic and therapeutic strategies for targeting retinal diseases.